How to kill a monster - Stine, R. L. (New York : Scholastic Inc., 1996)
Gretchen and her stepbrother, Clark, hate staying at their grandparents' house. There's something odd about the upstairs room... the one that's locked.
"An Apple paperback"--T.p.
"A Parachute Press book"--T.p. verso.
RL4 008-012.
360
360
Accelerated Reader AR
Keywords: Grandparent and child -- Juvenile fiction; Swamps -- Juvenile fiction; Monsters -- Juvenile fiction; Horror fiction